Determining the optimum conditions for bioemulsifier produced by Rhizobium leguminosarum biovar viciae isolated from Vicia faba root nodules - Ahmed , Suaad Ali (Iraqi Journal of Science, 2022)
The tested isolate of Rhizobium leguminosarum bv. viciae was isolated from root nodules of vicia faba plant from Baghdad ,the isolated bacteria was examined for bioemulsifier production when growing in mineral salt medium that containing 1% sunflower oil as sole carbon source . Rhizobium isolate was able to produce bioemulsifier with initial emulsification index E24% was 38%. Many of physical and nutritional cultural conditions for optimum emulsifier production was examined including : pH , temperature ,incubation period ,carbon and nitrogen source. The maximum bioemulsifier production form Rhizobium isolate was 64.5% when bacteria growing in mineral salt medium with pH 9 ,incubated at temperature 30 ºC , incubation period was 10 days ,the best carbon and nitrogen sources was sesame oil and NH4NO3 respectively .